Lithography-free fabrication of low operating voltage and large channel length graphene transistor with current saturation by utilizing Li+of ion-conducting-oxide gate dielectric - Chourasia N.K.; Singh V.K.; Sharma A.; Srivastava A.; Pal B.N. (My University, 2025)
The large channel length graphene field-effect transistor (GFET) can outperform its competitors due to its larger active area and lower noise. Such long channel length devices have numerous applications, e.g., in photodetectors, biosensors, etc. However, long channel length graphene devices are not common due to their semi-metallic nature. Here, we fabricate large channel length (up to 5.7 mm) GFETs through a simple, cost-effective method that requires thermally evaporated source-drain electrode deposition, which is less cumbersome than the conventional wet-chemistry based photolithography. The semiconducting nature of graphene has been achieved by utilizing the Li+ ion of the Li5AlO4 gate dielectric, which shows current saturation at a low operating voltage (∼2 V). The length scaling of these GFETs has been studied with respect to channel length variation within a range from 0.2 mm to 5.7 mm. It is observed that a GFET of 1.65 mm channel length shows optimum device performance with good current saturation. This particular GFET shows a "hole"mobility of 312 cm2 V-1 s-1 with an on/off ratio of 3. For comparison, another GFET has been fabricated in the same geometry by using a conventional SiO2 dielectric that does not show any gate-dependent transport property, which indicates the superior effect of Li+ of the ionic gate dielectric on current saturation. © 2020 Author(s).